I Got My Eyes on You: Examination of Sports Celebrity Endorsement Effect on Viewer s Visual Attention - B ¼y ¼kakg ¼l, mit Can; Y ¼ce, Arif; KatÄ±rcÄ±, Hakan (Jurnal The Messenger, 2021)
Celebrity endorsement is a widely used method to gather customer visual attention to the advertised product. Viewers' visual attention to the products is clinical for advertisers. This is why advertisers keep their eyes on consumers to know where they're looking. The study was aimed to explore the visual attention of young sports consumers by gender with the help of an eye-tracking system. An experiment was conducted with twenty-eight university students by using Tobii Pro Glasses-2 eye tracker. Fixation durations, counts, and areas were measured to assess the effects of sports celebrity endorsement on visual attention. In major findings, although in the ad where a female sports celebrity was featured, men and women respondents were fixed in similar areas, the men respondents put the maximum focus on the female athlete herself, while the women respondents focus maximum on the product. The present study found that the visual attention of the young sports consumers visual attention to the printed advertisements with sports contents varied by gender. Young consumers can have different connections and associations with celebrities than older consumers. The study gives important information to understand the young sports consumers visual attention to the printed advertisements which use sport celebrity endorsements.